Durian shell biological hard carbon material for negative electrode of sodium ion battery and preparation method of durian shell biological hard carbon material
By using durian shell biohard carbon material as the negative electrode material of sodium ion battery, the problem of insufficient capacity and performance of sodium ion battery is solved, high specific capacity and excellent low temperature performance are achieved, and the market demand for high-performance energy storage materials is met.
Patent Information
- Application Number
- CN202510076951.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The capacity performance of sodium ion batteries is limited by the difficulty of effectively accommodating and detaching sodium ions between layers of traditional graphite negative electrode materials, resulting in low energy storage efficiency of sodium ion batteries.
Durian shell biohard carbon material is used as the negative electrode material for sodium ion batteries. The specific surface area and sodium storage capacity of the material are improved by a preparation method including washing, drying, crushing, alkaline soaking, acid soaking, low-temperature lyophilization, low-temperature preoxidation, and Joule thermal oxygen-free high-temperature calcination.
It improves the specific capacity and circulation performance of sodium ion batteries, significantly improves the first-term effect and low-temperature performance of the battery, and meets the market's demand for high-performance and low-cost energy storage materials.
Smart Images

Figure CN119569035A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a durian shell bio-hard carbon material for a negative electrode of a sodium ion battery and a preparation method thereof. Background Art
[0002] Although lithium-ion batteries dominate the market and are widely used in various fields, the dilemma of high dependence on imported lithium resources has prompted us to explore more diversified energy storage solutions. As an emerging force, sodium-ion batteries are beginning to emerge in the market.
[0003] Given the global abundance and cost-effectiveness of sodium resources, as well as the similar working principles of sodium-ion batteries and lithium-ion batteries, the industry is increasingly looking forward to sodium-ion batteries, hoping that they can replace or assist lithium-ion batteries in certain application scenarios. However, the larger volume of sodium ions (about 0.1nm) compared to lithium ions (about 0.06nm) poses a challenge to traditional graphite negative electrode materials, because its interlayer spacing is difficult to effectively accommodate the insertion and extraction of sodium ions, which seriously limits the capacity performance of sodium-ion batteries.
[0004] After in-depth research, it was found that hard carbon materials show great potential in the negative electrode of sodium ion batteries. Different from the lithium storage mechanism of graphite, the sodium storage mechanism of hard carbon is more complex and diverse, which has not yet been fully resolved, but the generally recognized mechanisms include various reaction types such as intercalation, alloying and conversion. The unique structure of hard carbon, such as surface defects, interlayer gaps and micropores, provides a wide storage space for sodium ions, making it the preferred negative electrode material for sodium ion batteries. More importantly, hard carbon materials converted from biomass are not only abundant in resources and low in cost, but also have environmental advantages, and their preparation process is relatively simple. This material shows positive effects in improving the Coulomb efficiency and conductivity of sodium ion batteries, meeting the market demand for high-performance, low-cost energy storage materials. Considering the cost, environmental performance and practical application effects, biomass-derived carbon materials are undoubtedly the ideal choice for negative electrode materials for sodium ion batteries. Their structural controllability and performance optimizability provide broad space for the development of future energy storage technologies.
[0005] The patent No. 202211276795.X proposes a durian shell-based hard carbon negative electrode material and a preparation method thereof, wherein the steps of the preparation method include: (1) soaking the dried durian shell powder in hot water and acid successively, filtering, and drying to obtain a precursor powder; (2) pre-carbonizing the precursor powder under an inert atmosphere to obtain an intermediate product; (3) the intermediate product is first soaked in an alkaline solution, then soaked in an acid, washed to neutrality, and dried to obtain a purified product; (4) the purified product is carbonized under an inert atmosphere to obtain a durian shell-based hard carbon negative electrode material. The present invention uses biological waste durian shell as raw material, which is environmentally friendly and low in cost; the prepared durian shell-based hard carbon negative electrode material is conducive to ion storage, has a high specific capacity and excellent low-temperature performance. The patent uses a traditional tubular furnace carbonization process. From the scanning electron microscope image, it can be seen that the hard carbon material prepared by it has a small pore structure and the specific surface area needs to be further improved. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a durian shell bio-hard carbon material for sodium ion battery negative electrode and a preparation method thereof. The preparation method has a simple process flow, low cost, and is environmentally friendly. The sodium ion battery assembled with the sodium ion battery negative electrode made of the material has the advantages of high specific capacity, significant improvement in first efficiency, and excellent cycle performance.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] One of the technical solutions of the present invention:
[0009] A method for preparing a durian shell bio-hard carbon material comprises the following steps: washing, drying, crushing, alkali soaking, acid soaking, washing to neutrality and low-temperature freeze-drying of fresh durian shell, and then sequentially subjecting the shell to low-temperature pre-oxidation and high-temperature calcination without oxygen using a Joule heat method to obtain the durian shell bio-hard carbon material.
[0010] Furthermore, in the preparation method of durian shell biological hard carbon material, the temperature of the low-temperature pre-oxidation is 200-450°C, the time is 4-12h, and the Joule heat method oxygen-free low-temperature pre-carbonization process is carried out in a muffle furnace to achieve preliminary sintering and pore formation.
[0011] Furthermore, in the preparation method of durian shell biological hard carbon material, the temperature of the oxygen-free high-temperature calcination by Joule heat method is 900-1500°C, the time is 0.5-2h, and the oxygen-free high-temperature calcination process by Joule heat method is carried out in a Joule rapid heating furnace.
[0012] Furthermore, in the preparation method of durian shell bio-hard carbon material, the acid solution used in the acid soaking includes one or more of sulfuric acid, hydrochloric acid and hydrofluoric acid solution, and the alkaline solution used in the alkali soaking includes one or more of sodium hydroxide, potassium hydroxide and ammonia solution, and the concentration of the acid solution or the alkaline solution is 0.2-6 mol / L.
[0013] Furthermore, in the method for preparing durian shell biological hard carbon material, the durian shell accounts for 10-50% of the mass of the alkaline solution or the acid solution.
[0014] Furthermore, in the preparation method of the durian shell bio-hard carbon material, the low-temperature freeze-drying treatment time is 12-72 hours, and the temperature is -98°C to -50°C. Freeze-drying can effectively retain the original carbon structure of the biomass material, so that it avoids the shortcomings of carbon skeleton shrinkage and pore shrinkage caused by drying, thereby increasing the specific surface area of the carbon material and improving the sodium storage capacity of the hard carbon.
[0015] The second technical solution of the present invention:
[0016] A durian shell biological hard carbon material is prepared according to the preparation method.
[0017] The third technical solution of the present invention:
[0018] The application of the durian shell biological hard carbon material in preparing a negative electrode sheet of a sodium ion battery.
[0019] The fourth technical solution of the present invention:
[0020] A battery negative electrode sheet for a sodium ion battery comprises the durian shell bio-hard carbon material. The durian shell bio-hard carbon material is mixed with conductive carbon black and an adhesive, and stirred evenly to obtain an electrode slurry; the electrode slurry is applied on a current collector, dried and then rolled to obtain the negative electrode sheet.
[0021] Compared with the prior art, the present invention has the following advantages and technical effects:
[0022] (1) The method provided by the present invention uses durian shells, which are abundant in source and environmental waste, as raw materials, has low cost, is energy-saving and environmentally friendly, and can be recycled and reused.
[0023] (2) The process flow of the present invention is short, which greatly improves process efficiency and saves costs, thus facilitating industrialization.
[0024] (3) The durian shell bio-hard carbon negative electrode material prepared by the present invention has good sodium storage capacity. In battery applications, sodium ions can be effectively deintercalated in the negative electrode. The sodium ion battery assembled from the prepared sodium ion battery negative electrode has the advantages of high specific capacity, significant improvement in first efficiency, and excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0026] Figure 1 The SEM images of the durian shell bio-hard carbon material prepared in Example 1 and Comparative Example 1, wherein A) and B) are SEM images of the durian shell bio-hard carbon material at different magnifications of Example 1, and C) and D) are SEM images of the durian shell bio-hard carbon material at different magnifications of Comparative Example 1;
[0027] Figure 2 The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Example 1 as a raw material;
[0028] Figure 3 The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Comparative Example 1 as a raw material;
[0029] Figure 4 The first three charge and discharge results of the sodium ion battery prepared in Example 1 and Comparative Example 1, wherein A)-C) respectively represent the first three charge and discharge results of the sodium ion battery prepared in Example 1, and D)-F) respectively represent the first three charge and discharge results of the sodium ion battery prepared in Comparative Example 1;
[0030] Figure 5 The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Example 2 as a raw material;
[0031] Figure 6 The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Example 4 as a raw material;
[0032] Figure 7 The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Comparative Example 2 as a raw material;
[0033] Figure 8 The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Comparative Example 3 as a raw material;
[0034] Fig. 9 The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Comparative Example 4 as a raw material;
[0035] Fig.10 The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Comparative Example 5 as a raw material;
[0036] Fig.11The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Comparative Example 6 as a raw material;
[0037] Fig.12 This is the cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Example 3 as raw material. DETAILED DESCRIPTION
[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0039] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0043] The embodiment of the present invention provides a method for preparing a durian shell bio-hard carbon material, which comprises washing, drying, crushing, soaking in alkali, soaking in acid, washing to neutrality and freeze-drying the fresh durian shell, and then sequentially undergoing low-temperature pre-oxidation and high-temperature calcination without oxygen using Joule heat to obtain the durian shell bio-hard carbon material.
[0044] In a preferred embodiment of the present invention, the freeze-drying time is 12-72 hours, and the temperature is -98°C to -50°C. Freeze-drying can effectively retain the original carbon structure of the biomass material, so that it avoids the shortcomings of carbon skeleton shrinkage and pore shrinkage caused by drying, thereby increasing the specific surface area of the carbon material and improving the sodium storage capacity of the hard carbon.
[0045] In a preferred embodiment of the present invention, the temperature of the low-temperature pre-oxidation is 200-450°C, and the time is 4-12h. For example, the temperature of the low-temperature pre-oxidation can be 200°C, 250°C, 300°C, 350°C, 400°C or 450°C, and the time can be 4h, 6h, 8h, 10h or 12h. Within the above temperature and time ranges, the release of volatile substances in the biomass raw materials can be reduced, so that more carbon elements are retained in the solid product, and at the same time, the hydrogen bonds of cellulose, hemicellulose and lignin in the biomass material are broken, and some functional group oxidation gases escape, forming a rich pore structure, thereby increasing the yield and purity of hard carbon and electrochemical performance.
[0046] The Joule heat method low-temperature pre-oxidation process is carried out in a muffle furnace to achieve preliminary sintering and pore formation. Appropriate temperature can improve the carbonization efficiency of the material, improve the microstructure, increase the porosity, increase the specific surface area, and improve the stability of hard carbon.
[0047] In a preferred embodiment of the present invention, the temperature of the oxygen-free high-temperature calcination by Joule heat method is 900-1500°C, and the time is 0.5-2h, and the oxygen-free high-temperature calcination process by Joule heat method is carried out in a Joule rapid heating furnace. For example, the temperature of the oxygen-free high-temperature calcination by Joule heat method can be 900°C, 1000°C, 1100°C, 1200°C, 1400°C or 1500°C, and the time can be 0.5h, 1h, 1.5h, 1.8h or 2h, and the initial sintering and pore formation can be achieved within the above oxygen-free high-temperature calcination temperature and time range.
[0048] The oxygen-free high-temperature calcination process using Joule heat is a secondary calcination process that can effectively fix carbon, making the cycle performance of the negative electrode material more stable during the charge and discharge process. Secondly, it can further increase the pore structure of the carbon material, thereby improving the battery capacity. The use of Joule heat can accelerate this process and better fix carbon, increase the yield, and increase the specific surface area of the product, thereby improving the performance of the sodium-ion battery assembled from the negative electrode material.
[0049] In a preferred embodiment of the present invention, the acid solution used in the acid soaking includes one or more of sulfuric acid, hydrochloric acid and hydrofluoric acid solutions, and the alkaline solution used in the alkaline soaking includes one or more of sodium hydroxide, potassium hydroxide and ammonia solution, and the concentration of the acid solution or the alkaline solution is 0.2-6 mol / L.
[0050] In a preferred embodiment of the present invention, the mass proportion of the durian shell in the alkaline solution or the acid solution is 10-50%, and there is no special limitation, as long as the durian shell is immersed.
[0051] The embodiment of the present invention also provides a durian shell biological hard carbon material prepared according to the above preparation method, which is prepared according to the above preparation method.
[0052] All raw materials used in the examples of the present invention are commercially available.
[0053] The technical solution of the present invention is further illustrated by the following embodiments.
[0054] Example 1
[0055] (1) washing the durian shell with deionized water, cutting it into small pieces (with a diameter of 1 cm-3 cm), and shaking it in an ultrasonic machine for 30 min, then rinsing it with deionized water and drying it at 60° C., and grinding it into powder with a wall breaking machine to obtain a durian shell powder material (particle size <13 μm);
[0056] (2) The above-mentioned durian shell powder raw material is placed in a 500 mL beaker, deionized water is added to cover the sample, and the sample is placed in an 80° C. oil bath pot for 2 hours, and then transferred to a 2 mol / L NaOH solution, stirred and soaked at 60° C. for 2 hours, and then washed to neutrality, and then transferred to a 2 mol / L HCl solution, stirred and soaked at 60° C. for 2 hours, and then washed to neutrality, and then frozen in a refrigerator and placed in a -98° C. freeze dryer for low-temperature freeze drying for 36 hours. After freeze drying, a durian shell powder precursor is obtained;
[0057] (3) transferring the obtained durian shell powder precursor into a muffle furnace, heating it to 300° C. in an air atmosphere and keeping it at that temperature for 10 h to obtain pre-pyrolysis carbon;
[0058] (4) grinding the obtained pre-pyrolyzed carbon into powder, and passing it through a 1000-mesh sieve to obtain an intermediate;
[0059] (5) The obtained intermediate is transferred into a Joule rapid heating furnace filled with nitrogen, and the temperature is rapidly raised to 1300° C. and kept at this temperature for 2 h to obtain the durian shell bio-hard carbon material.
[0060] Example 2
[0061] (1) washing the durian shell with deionized water, cutting it into small pieces (with a diameter of 1 cm-3 cm), and shaking it in an ultrasonic machine for 30 min, then rinsing it with deionized water and drying it at 60° C., and grinding it into powder with a wall breaking machine to obtain a durian shell powder material (particle size <13 μm);
[0062] (2) The above-mentioned durian shell powder raw material was placed in a 500 mL beaker, deionized water was added to cover the sample, and the sample was placed in an 80°C oil bath for 2 h. Then, the sample was transferred to a 2 mol / L KOH solution, stirred and soaked at 60°C for 2 h, and then washed until neutral. The sample was transferred to a 2 mol / L H 2 SO 4 The solution was stirred and soaked at 60°C for 2 hours, then washed to neutrality, frozen in a refrigerator, and placed in a -98°C freeze dryer for 48 hours. After freeze drying, the durian shell powder precursor was obtained;
[0063] (3) The obtained durian shell powder precursor is transferred into a muffle furnace, heated to 400° C. in an air atmosphere, and kept at this temperature for 12 h to obtain pre-pyrolysis carbon;
[0064] (4) grinding the obtained pre-pyrolyzed carbon into powder, and passing it through a 1000-mesh sieve to obtain an intermediate;
[0065] (5) The obtained intermediate is transferred into a Joule rapid heating furnace filled with nitrogen, and the temperature is rapidly raised to 900° C. and kept at this temperature for 2 h to obtain the durian shell bio-hard carbon material.
[0066] Example 3
[0067] (1) washing the durian shell with deionized water, cutting it into small pieces (with a diameter of 1 cm-3 cm), and shaking it in an ultrasonic machine for 30 min, then rinsing it with deionized water and drying it at 60° C., and grinding it into powder with a wall breaking machine to obtain a durian shell powder material (particle size <13 μm);
[0068] (2) The above-mentioned durian shell powder raw material is placed in a 500 mL beaker, deionized water is added to cover the sample, and the sample is placed in an 80° C. oil bath pot for 2 hours, and then transferred to 2 mol / L NaOH, stirred and soaked at 60° C. for 2 hours, and then washed to neutrality, and then transferred to 2 mol / L HCL solution, stirred and soaked at 60° C. for 2 hours, and then washed to neutrality, and then frozen in a refrigerator and placed in a -98° C. freeze dryer for low-temperature freeze drying for 60 hours, and the durian shell powder precursor is obtained after freeze drying the water;
[0069] (3) The obtained durian shell powder precursor is transferred into a muffle furnace, heated to 450° C. in an air atmosphere and kept at this temperature for 2 h to obtain pre-pyrolysis carbon;
[0070] (4) grinding the obtained pre-pyrolyzed carbon into powder, and passing it through a 1000-mesh sieve to obtain an intermediate;
[0071] (5) The obtained intermediate is transferred into a Joule rapid heating furnace filled with nitrogen, and the temperature is rapidly raised to 1500° C. and kept at this temperature for 0.5 h to obtain the durian shell bio-hard carbon material.
[0072] Example 4
[0073] (1) washing the durian shell with deionized water, cutting it into small pieces (with a diameter of 1 cm-3 cm), and shaking it in an ultrasonic machine for 30 min, then rinsing it with deionized water and drying it at 60° C., and grinding it into powder with a wall breaking machine to obtain a durian shell powder material (particle size <13 μm);
[0074] (2) The above-mentioned durian shell powder raw material is placed in a 500 mL beaker, deionized water is added to cover the sample, and the sample is placed in an 80° C. oil bath pot for 2 hours, and then transferred to 4 mol / L NaOH, stirred and soaked at 60° C. for 2 hours, and then washed to neutrality, and then transferred to 4 mol / L HCL solution, stirred and soaked at 60° C. for 2 hours, and then washed to neutrality, and then frozen in a refrigerator and placed in a -98° C. freeze dryer for low-temperature freeze drying for 72 hours. After freeze-drying the water, a durian shell powder precursor is obtained;
[0075] (3) The obtained durian shell powder precursor is transferred into a muffle furnace, heated to 250° C. in an air atmosphere, kept at this temperature for 6 h, and fired to obtain pre-pyrolysis carbon;
[0076] (4) grinding the obtained pre-pyrolyzed carbon into powder, and passing it through a 1000-mesh sieve to obtain an intermediate;
[0077] (5) The obtained intermediate was transferred into a Joule rapid heating furnace filled with nitrogen, and the temperature was rapidly raised to 1100° C. and kept at this temperature for 1.5 h to obtain the durian shell bio-hard carbon material.
[0078] Comparative Example 1
[0079] (1) washing the durian shell with deionized water, cutting it into small pieces (with a diameter of 1 cm-3 cm), and shaking it in an ultrasonic machine for 30 min, then rinsing it with deionized water and drying it at 60° C., and grinding it into powder with a wall breaking machine to obtain a durian shell powder material (particle size <13 μm);
[0080] (2) The above-mentioned durian shell powder raw material is placed in a 500 mL beaker, deionized water is added to cover the sample, and the mixture is placed in an 80° C. oil bath for 2 h, and then transferred to a 2 mol / L NaOH solution, stirred and soaked at 60° C. for 2 h, washed until neutral, frozen in a refrigerator, and placed in a -98° C. freeze dryer for 24 h. After freeze drying, a durian shell powder precursor is obtained;
[0081] (3) The obtained durian shell powder precursor is transferred into a muffle furnace, heated to 300° C. in an air atmosphere, and kept at this temperature for 8 h to obtain pre-pyrolysis carbon;
[0082] (4) The obtained pre-pyrolysis carbon is ball-milled into powder and passed through a 1000-mesh sieve to obtain the durian shell bio-hard carbon material.
[0083] Comparative Example 2
[0084] (1) washing the durian shell with deionized water, cutting it into small pieces (with a diameter of 1 cm-3 cm), and shaking it in an ultrasonic machine for 30 min, then rinsing it with deionized water and drying it at 60° C., and grinding it into powder with a wall breaking machine to obtain a durian shell powder material (particle size <13 μm);
[0085] (2) The above-mentioned durian shell powder raw material is placed in a 500 mL beaker, deionized water is added to cover the sample, and the sample is placed in an 80° C. oil bath pot for 2 hours, and then transferred to 2 mol / L NaOH, stirred and soaked at 60° C. for 2 hours, and then washed to neutrality, and then transferred to 2 mol / L HCL solution, stirred and soaked at 60° C. for 2 hours, and then washed to neutrality, and then frozen in a refrigerator and placed in a -98° C. freeze dryer for low-temperature freeze drying for 12 hours. After freeze drying, the durian shell powder precursor is obtained;
[0086] (3) ball-milling the obtained durian shell powder precursor into powder, and passing it through a 1000-mesh sieve to obtain an intermediate;
[0087] (4) The obtained intermediate is transferred into a Joule rapid heating furnace filled with nitrogen, and the temperature is rapidly raised to 1300° C. and kept at this temperature for 2 h to obtain the durian shell bio-hard carbon material.
[0088] Comparative Example 3
[0089] The same as Example 1, except that in step (3), the obtained durian shell powder precursor is transferred into a muffle furnace, heated to 500° C. and kept at this temperature for 2 h to obtain pre-pyrolysis carbon.
[0090] Comparative Example 4
[0091] The same as Example 1, except that in step (3), the obtained durian shell powder precursor is transferred into a muffle furnace, heated to 150° C. and kept warm for 3 h to obtain pre-pyrolysis carbon.
[0092] Comparative Example 5
[0093] The same as Example 1, except that in step (5), the intermediate obtained is transferred into a Joule rapid heating furnace filled with nitrogen, heated to 2500° C. and kept warm for 0.5 h to obtain the durian shell bio-hard carbon material.
[0094] Comparative Example 6
[0095] The same as Example 1, except that in step (5), the intermediate obtained is transferred into a Joule rapid heating furnace filled with nitrogen, heated to 800° C. and kept warm for 2 h to obtain the durian shell bio-hard carbon material.
[0096] Performance Testing
[0097] The SEM images of the durian shell bio-hard carbon materials prepared in Example 1 and Comparative Example 1 are shown in Figure 1, A) and B) in the figure are SEM images of the durian shell bio-hard carbon material at different magnifications of Example 1, and C) and D) are SEM images of the durian shell bio-hard carbon material at different magnifications of Comparative Example 1. It can be seen that the durian shell bio-hard carbon material prepared in Example 1 has a large number of obvious honeycomb network structures, which is more conducive to the storage of sodium ions, while the durian shell bio-hard carbon material prepared in Comparative Example 1 has a smaller specific surface area, a more closed pore structure, and fewer surface active sites, which reflects that the battery performance prepared with this as raw material will be lower than that of Example 1.
[0098] The durian shell bio-hard carbon material prepared in the embodiment or comparative example is mixed with conductive carbon black (ketjen black) and a binder (PVDF, i.e. polyvinylidene fluoride) in a mass ratio of 8:1:1, and stirred evenly to obtain an electrode slurry; the obtained electrode slurry is applied on a current collector, dried and rolled to obtain a negative electrode sheet for a sodium ion battery, and the negative electrode sheet is further prepared into a sodium ion battery.
[0099] The prepared sodium ion battery was charged and discharged at a current density of 0.2 A / g. The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Example 1 as the raw material is shown in FIG. Figure 2 ,from Figure 2 It can be seen from the graph that the negative electrode sheet of the battery has good cycle stability and has a high capacity at a current density of 0.2A / g. The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Comparative Example 1 as raw material is shown in Figure 3 ,from Figure 3 It can be seen that the cycle stability of the negative electrode sheet of the battery is general, the first efficiency is much lower than that of Example 1, and the capacity is low at a current density of 0.2 A / g.
[0100] The first three charge and discharge results of the sodium ion battery prepared in Example 1 are shown in Figure 4 A)-C), the first three charge and discharge results of the sodium ion battery prepared in Comparative Example 1 are shown in Figure 4 D)-F) in the table represent comparative example 1, Figure 4 It can be seen that, in Example 1, except for the formation of SEI film in the first cycle, the curves of the second and third cycles are basically consistent, and the stability is good; secondly, due to the addition of the rapid heating furnace, the material defect structure increases, the pores are rich, and the capacity is improved in both the platform area and the climbing area. However, the capacity loss in the second and third cycles of Comparative Example 1 is relatively large.
[0101] Using the same method, the sodium ion batteries prepared in Example 2-4 and Comparative Example 2-6 were charged and discharged at a current density of 0.2 A / g, and the results were as follows:
[0102] The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Example 2 as raw material is shown in Figure 5 ,Depend on Figure 5 It can be seen that the secondary pyrolysis temperature of Example 2 is reduced, and the alkali treatment step is replaced with a more alkaline potassium hydroxide solution, so the capacity of the prepared battery is reduced. However, due to the high heating rate of the Joule fast reaction furnace, the pore structure is rich and the stability is acceptable.
[0103] The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Example 4 as raw material is shown in Figure 6 ,Depend on Figure 6 It can be seen that Example 4 increases the concentration of acid and alkali, making the surface active sites of the hard carbon negative electrode after etching rich and the sodium storage capacity strong, but the temperature decreases resulting in a reduction in the pore structure and average cycle performance.
[0104] The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Comparative Example 2 as raw material is shown in Figure 7 ,Depend on Figure 7 It can be seen that Example 4 adopts a one-step firing method and only performs high-temperature pre-firing, so the pore richness is far from enough. Although the cycle stability is acceptable, the capacity decreases significantly.
[0105] The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Comparative Example 3 as raw material is shown in Figure 8 ,Depend on Figure 8 It can be seen that comparative example 3 greatly increases the pre-oxidation temperature, resulting in a large waste of energy, and the pre-oxidation temperature may be too high, resulting in more carbon loss and poor capacity, but the cycle is relatively stable.
[0106] The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Comparative Example 4 as raw material is shown in Fig. 9 ,Depend on Fig. 9 It can be seen that comparative example 4 greatly reduces the pre-oxidation temperature. 150°C may just evaporate the water in the material, and the support and influence on the pore structure are negligible, so the capacity performance of the battery is poor.
[0107] The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Comparative Example 5 as raw material is shown in Fig.10 ,Depend on Fig.10 It can be seen that comparative example 5 greatly increases the secondary high-temperature pyrolysis temperature, and the battery cycle performance is also improved to a reasonable extent. However, the ultra-high temperature may lead to severe graphitization, resulting in poor battery stability. Moreover, the conditions are too harsh for mass production, and there is a large waste of resources.
[0108] The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Comparative Example 6 as raw material is shown in Fig.11 ,Depend on Fig.11It can be seen that in Comparative Example 6, the secondary high-temperature calcination temperature was reduced to 800°C, resulting in insufficient carbon fixation, and thus poor battery performance, low cycle and cycle stability, and even a serious drop after 25 cycles.
[0109] The cycle curve of the sodium ion battery prepared using the durian shell bio-hard carbon material of Example 3 as raw material is shown in Fig.12 , slightly increasing the secondary calcination temperature, the capacity is better and the stability is also better.
[0110] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a durian shell biological hard carbon material, characterized in that: The fresh durian shell is washed, dried, crushed, soaked in alkali, soaked in acid, washed to neutrality and freeze-dried at low temperature, and then sequentially subjected to low temperature pre-oxidation and Joule heat method oxygen-free high temperature calcination to obtain the durian shell bio-hard carbon material.
2. The method for preparing the durian shell biological hard carbon material according to claim 1, wherein The temperature of the low-temperature pre-oxidation is 200-450° C., and the time is 4-12 hours.
3. The method for preparing the durian shell biological hard carbon material according to claim 1, wherein The temperature of the oxygen-free high-temperature calcination by Joule heat method is 900-1500° C. and the time is 0.5-2 hours.
4. The method for preparing the durian shell biological hard carbon material according to claim 1, wherein The acid solution used in the acid soaking includes one or more of sulfuric acid, hydrochloric acid and hydrofluoric acid solutions, and the alkaline solution used in the alkaline soaking includes one or more of sodium hydroxide, potassium hydroxide and ammonia solution. The concentration of the acid solution or the alkaline solution is 0.2-6 mol / L.
5. The method for preparing the durian shell biological hard carbon material according to claim 1, wherein The low-temperature freeze-drying treatment lasts for 12-72 hours at a temperature of -98°C to -50°C.
6. A durian shell biological hard carbon material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 5.
7. Use of the durian shell biological hard carbon material as claimed in claim 6 in preparing a battery negative electrode sheet for a sodium ion battery.
8. A negative electrode sheet for a sodium ion battery, characterized in that: The invention comprises the durian shell biological hard carbon material as described in claim 6.
9. The negative electrode sheet for sodium ion battery according to claim 8, characterized in that: The durian shell biological hard carbon material is mixed with conductive carbon black and an adhesive, and stirred evenly to obtain an electrode slurry; the electrode slurry is applied on a current collector, and the battery negative electrode sheet for the sodium ion battery is obtained by rolling after drying.
Citation Information
Patent Citations
Sodium-ion battery carbon negative electrode material prepared based on waste wood chips and preparation method thereof
CN113651307A
Durian shell-based hard carbon negative electrode material and preparation method thereof
CN115650202A
Ultrafast preparation method of sodium ion battery hard carbon negative electrode material
CN116462176A
Preparation method and application of biomass hard carbon negative electrode material of sodium-ion battery
CN116692858A
Preparation method and application of sodium ion battery hard carbon material
CN116947038A